2013
DOI: 10.1007/s00125-012-2813-9
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A inhibits pro-inflammatory cytokine-induced damage to islets in culture and following transplantation

Abstract: Aims/hypothesis Beta cell death triggered by pro-inflammatory cytokines plays a central role in the pathogenesis of type 1 diabetes and loss of transplanted islets. The nuclear factor κB (NF-κB) signalling pathway is a key regulator of beta cell stress response, survival and apoptosis. Withaferin A (WA), a steroidal lactone derived from Withania somnifera, has been demonstrated to be a potent, safe, anti-inflammatory molecule that can inhibit NF-κB signalling. Therefore, we evaluated the ability of WA to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 47 publications
(70 reference statements)
0
40
0
Order By: Relevance
“…In the previous studies, treatment of WFA inhibited inflammatory cytokine secretion in human and mouse islets (27). Also, WFA inhibited inflammation via inhibition of NO production and iNOS expression by blocking Akt and subsequently down-regulating NF-kB activity in RAW 264.7, a mouse leukemic monocyte macrophage cell line (28).…”
Section: Discussionmentioning
confidence: 86%
“…In the previous studies, treatment of WFA inhibited inflammatory cytokine secretion in human and mouse islets (27). Also, WFA inhibited inflammation via inhibition of NO production and iNOS expression by blocking Akt and subsequently down-regulating NF-kB activity in RAW 264.7, a mouse leukemic monocyte macrophage cell line (28).…”
Section: Discussionmentioning
confidence: 86%
“…Results are averages ± SE of 5 individual biological repeats. cells and protecting against cytokine induced damage (Peng et al, 2010;SoRelle et al, 2013), the role of withaferin A as an insulin mimetic is quite novel. In addition, W. somnifera's insulin secretagogue activity is also surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Kobuyama T et al,2002 [32] illustrated therapeutic potential of withanolide A isolated from root of Ws, that possess ability to regenerate neurites and reconstruct synapses in severly damaged neurons in mice. Amongst withanolides of Ws, withaferin A, a major component of biologically active steroids, showed potent anti-inflammatory [33] and anti-cancerous activity [34]. Thus, the study revealed the pharmacological potential of Ws, which could be harnessed in future, for the therapeutic approaches to PD.…”
Section: Introductionmentioning
confidence: 88%